Evolutionary relationships and biogeography of Biomphalaria (Gastropoda: Planorbidae) with implications regarding its role as host of the human bloodfluke, Schistosoma mansoni (2001)
ABSTRACT: The wide geographic distribution of Schistosoma mansoni, a digenetic trematode and parasite of humans, is determined by the occurrence of its intermediate hosts, freshwater snails of the genus Biomphalaria (Preston 1910). We present phylogenetic analyses of 23 species of Biomphalaria, 16 Neotropical and seven African, including the most important schistosome hosts, using partial mitochondrial ribosomal 16S and complete nuclear ribosomal ITS1 and ITS2 nucleotide sequences. A dramatically better resolution was obtained by combining the data sets as opposed to analyzing each separately, indicating that there is additive congruent signal in each data set. Neotropical species are basal, and all African species are derived, suggesting an American origin for the genus. We confirm that a proto-Biomphalaria glabrata gave rise to all African species through a trans-Atlantic colonization of Africa. In addition, genetic distances among African species are smaller compared with those among Neotropical species, indicating a more recent origin. There are two species-rich clades, one African with B. glabrata as its base, and the other Neotropical. Within the African clade, a wide-ranging tropical savannah species, B. pfeifferi, and a Nilotic species complex, have both colonized Rift Valley lakes and produced endemic lacustrine forms. Within the Neotropical clade, two newly acquired natural hosts for S. mansoni (B. straminea and B. tenagophila) are not the closest relatives of each other, suggesting two separate acquisition events. Basal to these two species-rich clades are several Neotropical lineages with large genetic distances between them, indicating multiple lineages within the genus. Interesting patterns occur regarding schistosome susceptibility: (1) the most susceptible hosts belong to a single clade, comprising B. glabrata and the African species, (2) several susceptible Neotropical species are sister groups to apparently refractory species, and (3) some basal lineages are susceptible. These patterns suggest the existence of both inherent susceptibility and resistance, but also underscore the ability of S. mansoni to adapt to and acquire previously unsusceptible species as hosts. Biomphalaria schrammi appears to be distantly related to other Biomphalaria as well as to Helisoma, and may represent a separate or intermediate lineage.